2015
DOI: 10.1007/s12094-015-1298-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of ERCC1 polymorphisms (rs3212986 and rs11615) with the risk of head and neck carcinomas based on case–control studies

Abstract: The findings of the meta-analysis indicated that a decreased risk for the ERCC1 rs3212986 polymorphism was found among Asians, and an increased risk for the ERCC1 rs11615 polymorphism was found in overall HNSCC, especially in Asian subgroup and laryngeal site, suggesting that ERCC1 rs3212986 polymorphism in Asians may act as a protective factor and rs11615 polymorphism may be a risk factor for HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…This study included 910 head and neck cancer patients and 1337 control subjects from seven trials. The authors of that study concluded that the ERCC1-rs3212986 polymorphism in Asian populations was a predictor of head and neck cancer, whereas the ERCC1-rs11615 polymorphism was a risk factor for head and neck tumours, particularly laryngeal tumours 25 . One study investigated eight nucleotide polymorphisms of six genes in the context of smoking-related laryngeal squamous carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…This study included 910 head and neck cancer patients and 1337 control subjects from seven trials. The authors of that study concluded that the ERCC1-rs3212986 polymorphism in Asian populations was a predictor of head and neck cancer, whereas the ERCC1-rs11615 polymorphism was a risk factor for head and neck tumours, particularly laryngeal tumours 25 . One study investigated eight nucleotide polymorphisms of six genes in the context of smoking-related laryngeal squamous carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, baseline biomarkers are evaluated for their prognostic role for disease outcomes (regardless of treatment), reflected by critical clinical trial endpoints. Key endpoints include overall survival (OS), progression‐free survival (PFS), disease‐free survival (DFS), loco‐regional (LR) control, and distant metastasis‐free survival …”
Section: Prognostic and Predictive Biomarkersmentioning
confidence: 99%
“…DNA variants in MLH1 , which is involved in mismatch repair systems, are known to cause the hereditary cancer disorder ‘Lynch syndrome’ and also confer susceptibility to azoospermia and oligozoospermia (58, 59). Interestingly, an identical mutation C8092A (rs3212986) in the DNA base excision repair gene ERCC1 has independently been linked to both idiopathic azoospermia (60) and various types of cancer, including breast carcinoma, head and neck carcinoma and adult glioma (6163). No studies have performed a mutational screening of these genes in male infertility cases with cancer as a comorbid state.…”
Section: Heritable Susceptibility To Cancer and Male Infertilitymentioning
confidence: 99%